2015
DOI: 10.1093/cvr/cvv229
|View full text |Cite
|
Sign up to set email alerts
|

Neuropilins 1 and 2 mediate neointimal hyperplasia and re-endothelialization following arterial injury

Abstract: AimsNeuropilins 1 and 2 (NRP1 and NRP2) play crucial roles in endothelial cell migration contributing to angiogenesis and vascular development. Both NRPs are also expressed by cultured vascular smooth muscle cells (VSMCs) and are implicated in VSMC migration stimulated by PDGF-BB, but it is unknown whether NRPs are relevant for VSMC function in vivo. We investigated the role of NRPs in the rat carotid balloon injury model, in which endothelial denudation and arterial stretch induce neointimal hyperplasia invol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
50
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(56 citation statements)
references
References 39 publications
6
50
0
Order By: Relevance
“…Similar mechanisms have been described for PDGFRβ (Hellberg et al, 2009;Karlsson et al, 2006), and NRP1, as well as NRP2, has been suggested to be involved in PDGFR downstream signal conduction (Pellet-Many et al, 2015). Our initial analysis did, however, not reveal changes in PDGF-D-PDGFRβ downstream signaling dependent on the presence or absence of NRP1.…”
Section: Pdgf-d Induces the Interaction Of Pdgfrβ And Nrp1 In Trans Bsupporting
confidence: 81%
See 1 more Smart Citation
“…Similar mechanisms have been described for PDGFRβ (Hellberg et al, 2009;Karlsson et al, 2006), and NRP1, as well as NRP2, has been suggested to be involved in PDGFR downstream signal conduction (Pellet-Many et al, 2015). Our initial analysis did, however, not reveal changes in PDGF-D-PDGFRβ downstream signaling dependent on the presence or absence of NRP1.…”
Section: Pdgf-d Induces the Interaction Of Pdgfrβ And Nrp1 In Trans Bsupporting
confidence: 81%
“…Despite reports of NRP1 interaction with PDGFs (Ball et al, 2010;Banerjee et al, 2006;Cao et al, 2010;Pellet-Many et al, 2011), a specific binding site for PDGFs in NRP1 is not known. In addition, interactions of NRP1 with PDGFRα or PDGFRβ have been suggested (Pellet-Many et al, 2015), but its potential role in PDGF-PDGFR signaling remains elusive.…”
Section: Introductionmentioning
confidence: 99%
“…Activation of the epicardium and subsequent regeneration involves multiple cellular processes, including cell migration, proliferation, and EMT. It is well established that NRP1 modulates cell migration in diverse mammalian cell types (29, [54][55][56][57]. The conclusion that nrp1a is important for zebrafish epicardial migration is supported by our finding that ex vivo outgrowth from epicardial explants of nrp1a sa1485/sa1485 hearts was also impaired.…”
Section: Analysis Of Mutant Nrp1a Sa1485/sa1485 Fish Lacking Expressisupporting
confidence: 80%
“…NRPs were first implicated in neuronal guidance, vasculogenesis and angiogenesis in the embryo via mediating signalling pathways driven by class 3 Semaphorins (SEMA3s) and Vascular Endothelial Growth Factor (VEGF), respectively [ 25 , 29 , 30 , 31 , 32 ]. However, NRPs are now known to partner with a wide variety of transmembrane receptors and therefore modulate numerous signalling pathways [ 23 , 24 ], including those activated by Epidermal Growth Factor (EGF) [ 33 ], Fibroblast Growth Factor (FGF) [ 34 ], Hepatocyte Growth Factor (HGF) [ 35 ], Insulin-like Growth Factor (IGF) [ 36 ], Platelet-Derived Growth Factor (PDGF) [ 37 , 38 ] and Transforming Growth Factor beta (TGFβ) [ 39 ]. As a result, NRPs mediate multiple cellular processes, and dysregulation of their activity has been implicated with several pathological conditions [ 23 , 38 , 40 , 41 , 42 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, NRPs are now known to partner with a wide variety of transmembrane receptors and therefore modulate numerous signalling pathways [ 23 , 24 ], including those activated by Epidermal Growth Factor (EGF) [ 33 ], Fibroblast Growth Factor (FGF) [ 34 ], Hepatocyte Growth Factor (HGF) [ 35 ], Insulin-like Growth Factor (IGF) [ 36 ], Platelet-Derived Growth Factor (PDGF) [ 37 , 38 ] and Transforming Growth Factor beta (TGFβ) [ 39 ]. As a result, NRPs mediate multiple cellular processes, and dysregulation of their activity has been implicated with several pathological conditions [ 23 , 38 , 40 , 41 , 42 ]. NRPs are expressed by ECs [ 31 ], leukocytes [ 24 ] and VSMCs [ 38 , 40 , 43 , 44 , 45 ] within the vasculature, and are emerging as multifaceted regulators of signalling pathways associated with CVD [ 23 ].…”
Section: Introductionmentioning
confidence: 99%